Population Density of Wolbachia Bacteria and the Induction of the Popcorn-Effect in Drosophila melanogaster - ENDANG SRIMURNI KUSMINTARSIH (Microbiology Indonesia, 2008)
Drosophila melanogaster is known to harbour Wolbachia bacteria that cause the early death of its adult host. The death occurs early as a result of cell rupture caused by the proliferation of Wolbachia within it. However, the number of Wolbachia causing the early death in D. melanogaster is unknown. In order to determine whether the number of Wolbachia is related to the early death of its host, the quantity of Wolbachia and nuclei were examined using the real-time PCR procedure. The results showed that an egg cell contains at least 2-3 bacterial cells. A 4 day old larva contains at least 45 cells. The number of Wolbachia in adult flies of 1, 5, 8, and 12 days old were 422, 535, 964, and 610 per host cell, respectively.